Concubinage in the Polish tax law - Aleksy Goettel (Contemporary Economics, 2021)
The main goal of this study is to assess whether, and if so, how the tax policy is implemented in Poland in relation to informal partnerships. The justification for conducting research in this area is the growing number of such relationships and the demands formulated by the public on the principles of taxation of cohabitants. The study analyzes not only taxes on natural persons, but also the provisions governing the principles of tax liability. The research shows that while pro-family tax policy is implemented on a fairly large scale in Poland, it does not apply to cohabitants. In principle, cohabitants do not have the right to any preferential taxation rules, above all tax reliefs and exemptions. Moreover, the analysis of the research material clearly indicates that staying in cohabitation can even aggravate the situation of a cohabitant under tax law (which can be seen perfectly well on the example of a cohabitant's liability for his partner's taxes). On the basis of a critical analysis of the Polish tax law provisions, the general thesis has been formulated that the situation of cohabitants is affected by deep asymmetry, because on the one hand the legislator uses cohabitation to improve the allocation of public revenues, but on the other hand it does not include cohabitants with pro-family tax policy (although cohabitation is very similar to marriage). The study includes certain demands on the legislator, thanks to which it is possible to cover cohabitants by pro-family tax policy.
Keywords: K34; K36; 330; Tax; tax policy; tax law; tax exemptions; tax reliefs; cohabitation; cohabitants; concubinage